If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 83 = 6(n + 3) + 7n Reorder the terms: 83 = 6(3 + n) + 7n 83 = (3 * 6 + n * 6) + 7n 83 = (18 + 6n) + 7n Combine like terms: 6n + 7n = 13n 83 = 18 + 13n Solving 83 = 18 + 13n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-13n' to each side of the equation. 83 + -13n = 18 + 13n + -13n Combine like terms: 13n + -13n = 0 83 + -13n = 18 + 0 83 + -13n = 18 Add '-83' to each side of the equation. 83 + -83 + -13n = 18 + -83 Combine like terms: 83 + -83 = 0 0 + -13n = 18 + -83 -13n = 18 + -83 Combine like terms: 18 + -83 = -65 -13n = -65 Divide each side by '-13'. n = 5 Simplifying n = 5
| (3x-7)(4x+7)=0 | | y=[x]2+8x | | 2x+16x+5=0 | | x-.17=504.23 | | 2x^2-y^2=41 | | r(-50)=0 | | x-.17x=504.23 | | x-3(10-3x)=100 | | 1=1-x-4x | | 16=1/2h^2 | | x-.24x=465.12 | | 0.06(x^2)+0.15y(30-x)=0.12(8x) | | 6r+5-3r=-4 | | (m+7)(m-8)= | | x-.24=465.12 | | 8m+19=-10 | | Log(9-4c)=2.5 | | -7p+2(-3p+2)=4(p+1) | | P=8n+4 | | 0.5/2a/3 | | 18=1-8p+1 | | 4+3n-8n=-3n-8+n+6 | | 8+6(6+6m)=116 | | 3h-1=5 | | 18-3n=4n+11 | | 13+8m=7m+14 | | w+15=2 | | 1-7y=2y-14 | | (2x)(x+4)=0 | | 5t+4r+9=0 | | 9+3.5f=11-0.5g | | 36+2y=-4y |